Perceived discrimination and refutation in the discourse of informal business women on the Peruvian-Chilean border - Pastor Seperak, Marly Mahly (2022)
This article analyzes the perceived discrimination discourse of peruvian women merchants of second-use clothing and footwear on the peruvian-chilean border. The activity they carry out is part of the small-value trade protected by a special border regime of the 1929 treaty, but today, after subsequent legislative processes, it is an informal, illegal and criminalized practice in Tacna (Peru). Based on the methodological proposal of David Mellor (2003) and Eugenia Merino (2006) for the Critical Discourse Analysis of Perceived Discrimination, it seeks to reveal, through their personal narratives, the way in which this group of merchants perceives their representation. and stigmatization. The survey of their life stories shows the pre-eminence of two main categories of discrimination, the «institutional» and the «verbal»; likewise, among the topics that make up these categories, the topic «prejudices» stands out, whose analysis of its argumentative sequence shows the constant use of refutation. From this, it can be concluded that in the discourse of the merchants there is full awareness of the representation of their otherness and an urgent need to refute the prejudices that exist about them and their work.